Misperceiving economic success: experimental evidence on meritocratic beliefs and inequality acceptance - Dietmar Fehr; Martin Vollmann (The Journal of Economic Inequality, 2025)
Meritocratic beliefs are often invoked as justification for inequality. We provide evidence on how meritocratic beliefs are shaped by economic rewards and how they contribute to the moral justification of inequality. In a large-scale survey experiment in the US, we show that economic rewards cause a change in beliefs about success depending on effort rather than luck. Exploiting exogenous variation in meritocratic beliefs in a two-stage analysis shows that these beliefs affect the level of inequality people accept. Successful people prefer to remain ignorant about the true underlying reasons for success, and there is no evidence that meritocratic beliefs are moderated by political orientation.
Keywords: 300; Meritocratic beliefs; Inequality acceptance; Fairness; Political views; Survey experiment